Sistem Kata Sapaan Kekerabatan dalam Bahasa Melayu di Kepenghuluan Bangko Kiri Rokan Hilir Riau - Sari, Nika; Ermanto, Ermanto; Nst., M. Ismail (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2013)
This article was written to (1) describing the form and used of greeting words in Melayu language based on lineage in Bangko kiri. (2) describing the form and used of greeting words in Melayu language based on marriage in Bangko Kiri. The data in this research consist of the idiom of language in sentence that followed by greeting words that’s belong there. The data has been collected by cakap method with pancing technique. The finding of this research is (1) the form and used of the greeting words based on patrilineal lineage, which are: there are sixteen form of greeting words that used for different ego. (2) Then there are twenty two the form of greeting words based on marriage line that has been use for different ego.